Bacterial contamination of mobile phones of health care workers at Jimma University Specialized Hospital, Jimma, South West Ethiopia - Misgana, Girma Mulisa; Abdissa, Ketema; Abebe, Gemeda (International Journal of Infection Control, 2015)
Millions of people worldwide are suffering from infections acquired in hospitals. Contaminated equipment and hospital environments are known sources of infection. Mobile phones are used in hospitals without restrictions, regardless of their unknown microbial load. This study aimed to determine the level of bacterial contamination of mobile phones of health care workers at Jimma University Specialized Hospital in comparison with non health care workers’ mobile phones.A cross-sectional comparative study was used to conduct this study. The pattern of mobile phone use and cleaning practice of study participants were assessed using a questionnaire. Swab specimens were collected from exposed known areas of mobile phones and eluted in sterile normal saline. Colonies were counted using calibrated wire loop technique and growths were identified following standard bacteriological technique. Kirby-Bauer disc diffusion method was used to determine the antimicrobial sensitivity tests of the isolates. Data analysis was performed using SPSS version 16A total of 71.2% (94/132) of mobile phones showed evidence of bacterial contamination from which 61.7% (58/94) were contaminated with >5colony forming units/cm2. The degree of bacterial contamination was higher among health care workers mobile phones (OR= 4.50; 95%CI 1.85-10.98). A total of 112 bacterial organisms were isolated with 33 Staphylococcus aureus, 61 coagulase negative staphylococci, 12 Bacillus species, 4 Micrococcus species, 1 Serratia species and 1 Klebsiella pneumonia. Thirty nine percent (5/13) of meticillin resistant S. aureus were vancomycin resistant. Health care workers mobile phones were more likely contaminated with meticillin resistant S. aureus than non health care workers’ mobile phones (OR=12.83; 95% CI 2.15-37.45). All of the study participants never wash their hands after mobile phone use and 75.5% (50/66) of health care workers answered that they used their mobile phones while attending patients. Health care workers mobile phones were more contaminated than non health care works’ mobile phones. The majority of the resistant isolates were from health care workers’ mobile phones.